1ISG-001 Can rivaroxaban become cost saving compared with vitamin K antagonists in the treatment of patients with non-valvular atrial fibrillation in France?. (24th March 2020) - Robert, S; Vincent, F; Vengadessane, S
Abstract : Background and importance: Non-valvular atrial fibrillation (NVAF) affects 750 000 people in France and is associated with significant morbidity, use of healthcare resources and costs. The randomised controlled trial ROCKET-AF demonstrated that rivaroxaban is an efficacious alternative to warfarin in patients with NVAF. The new oral anticoagulants (NOAC) appear to have an acceptable cost effectiveness ratio in France. But is it possible that rivaroxaban could remain cost effective with the introduction of generic drugs? Aim and objectives: To determine the price threshold for rivaroxaban to become cost effective compared with vitamin K antagonists (VKAs) in the treatment of NVAF, using real world evidence and from a French payer perspective. Material and methods: The annual cost differences associated with rivaroxaban use compared with VKAs among NVAF patients were estimated. Clinical events reflecting the efficacy and safety of the drugs were converted into costs. Drugs costs and VKA monitoring were added to obtain a total cost. Cost differences were then calculated with a price of rivaroxaban reduced by: 20% (reduction in the price of the brand name drug when the first generic is marketed)); 32.5% (total decrease in the price of the brand name drug 18–24 months after the first generic is marketed); 60% (price of a generic compared with the brand name drug). Event rates were obtained from the pragmatic study BROTHER. The annual costs for each clinical event and for VKA monitoring were obtained from the literature (studies in French setting). The cost of medicines in 2018 came from the French National Health Insurance database. Results: The total cost difference associated with the use of rivaroxaban instead of VKAs were estimated at +303€ per patient per year. The total cost differences were +124€, +12€ and −234€ with price decreases of 20%, 32.5% and 60%, respectively. The threshold for a cost saving with rivaroxaban was a 34% decrease in the price of the drug. Conclusion and relevance: Rivaroxaban can become cost saving with a 34% price reduction. The commercialisation of NOAC generics should allow them to play an even more important role in the treatment of NVAF. References and/or acknowledgements: No conflict of interest.